2018
DOI: 10.1097/inf.0000000000001919
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Diseases Consultation Improves Treatment and Decreases Mortality by Enterococcal Bacteremia in Children

Abstract: ID consultation was associated with a higher rate of appropriate therapy and may decrease mortality because of enterococcal bacteremia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Specifically, ID consultation in the treatment of enterococcal bacteremia was associated with lower 30-day mortality compared with patients who did not receive ID consultation, especially when Enterococcus faecium was isolated [ 9 ]. An additional retrospective analysis assessed the impact of ID consultation in children with enterococcal bacteremia [ 10 ]. This analysis showed ID specialist involvement to be associated with a significant improvement in outcomes, such as higher rates of appropriate empiric therapy, appropriate definitive therapy, and increased survival at 1 year [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, ID consultation in the treatment of enterococcal bacteremia was associated with lower 30-day mortality compared with patients who did not receive ID consultation, especially when Enterococcus faecium was isolated [ 9 ]. An additional retrospective analysis assessed the impact of ID consultation in children with enterococcal bacteremia [ 10 ]. This analysis showed ID specialist involvement to be associated with a significant improvement in outcomes, such as higher rates of appropriate empiric therapy, appropriate definitive therapy, and increased survival at 1 year [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation from Japan evaluated the impact of IDC on enterococcal bacteremia in children; ID consultations were significantly associated with appropriate empiric and definitive therapy, appropriate treatment duration, and lower risk of 1-year mortality [28]. Zasowski et al reported that IDC within 24 h was significantly associated with a lower risk for delayed appropriate therapy, and therefore with a lower 30-day mortality in 190 patients with enterococcal BSI [14].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have highlighted the value of pediatric infectious diseases specialists, which may range from outbreak recognition to improving mortality. [10][11][12] In established situations, such assets are intangible and may be underestimated. The relatively clear differences shown in our study, most likely reflect the emergence and recognition of pediatric infectious diseases as a clinical subspecialty in the past decade in Japan.…”
Section: Discussionmentioning
confidence: 99%